2013
DOI: 10.3390/nu5072384
|View full text |Cite
|
Sign up to set email alerts
|

Iron: Protector or Risk Factor for Cardiovascular Disease? Still Controversial

Abstract: Iron is the second most abundant metal in the Earth’s crust. Despite being present in trace amounts, it is an essential trace element for the human body, although it can also be toxic due to oxidative stress generation by the Fenton reaction, causing organic biomolecule oxidation. This process is the basis of numerous pathologies, including cardiovascular diseases (CVD). The relationship between iron and cardiovascular disease was proposed in 1981 by Jerome Sullivan. Since then, numerous epidemiological studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 59 publications
1
54
1
Order By: Relevance
“…The association of SBP with iron in our study, and its link to metabolic syndrome, is also supported by previous reports in the literature (DeBoer et al, 2012;Houschyar et al, 2012;Rajapurkar et al, 2012). There is also evidence for the higher serum iron levels, its association with oxidative stress (Muñoz-Bravo, Gutiérrez-Bedmar, Gómez-Aracena, García-Rodríguez, & Navajas, 2013), and the increased severity of atherosclerosis and coronary artery disease (Bagheri et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The association of SBP with iron in our study, and its link to metabolic syndrome, is also supported by previous reports in the literature (DeBoer et al, 2012;Houschyar et al, 2012;Rajapurkar et al, 2012). There is also evidence for the higher serum iron levels, its association with oxidative stress (Muñoz-Bravo, Gutiérrez-Bedmar, Gómez-Aracena, García-Rodríguez, & Navajas, 2013), and the increased severity of atherosclerosis and coronary artery disease (Bagheri et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…The reason is probably that people focus on the association between CVD and systemic iron status. The parameters tested generally include serum ferritin, iron, and hepcidin 30) . CVD, in the case of atherosclerosis, may display a focal iron deposition or accumulation in atherosclerotic plaques rather than a systemic iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excess iron could be harmful because it is able to catalyse the formation of highly reactive oxygen and hydrogen radicals when present in the unbound state. Transition metal ions, established catalysts of protein, lipid and DNA oxidation, are present at elevated levels in human atherosclerotic plaques, and in some animal models, consistent with the hypothesis that metal ions contribute to both plaque formation and its destabilization (19,21,23), though the role of metal ions remains controversial (16,29).…”
mentioning
confidence: 65%
“…On the other hand, excess iron could be harmful because it is able to catalyse the formation of highly reactive oxygen and hydrogen radicals when present in the unbound state. Transition metal ions, established catalysts of protein, lipid and DNA oxidation, are present at elevated levels in human atherosclerotic plaques, and in some animal models, consistent with the hypothesis that metal ions contribute to both plaque formation and its destabilization (19,21,23), though the role of metal ions remains controversial (16,29).Epidemiological studies have reported an increased incidence of cardiovascular disease (CVD) in subjects with overt iron overload (7,8,19). Recent studies on cardiovascular evaluation and outcome in high-versus low-frequency blood donors have demonstrated improvements in surrogate markers of vascular health such as decreased oxidative stress, and…”
mentioning
confidence: 65%